Green Employee Performance in Fish Canning Industry: the Relationship of Green Knowledge Sharing, Green Career Development, and Green Work Balance - Heriyanti, Sinta Sundari; Ismamudi; Bimanti Esthi, Raniasari; Ferawati, Neli (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The fish canning industry increasingly emphasizes sustainable business practices due to its significant environmental impact, especially through waste. Green business practices are key to maintaining the sustainability of marine resources. Employee involvement in green knowledge sharing (GKS) and green career development (GCD) is essential, as their contributions positively impact the company's green performance. Investment in employee development benefits both individuals and the company's sustainability. In addition, green work-life balance (GWB) also plays an important role in improving employee green performance (GEP). This study examines the effect of GKS and GCD on GEP with GWB as a mediator. A quantitative approach was used, with the study population covering employees in the fish canning industry. The purposive sampling method was applied to Karawang Regency, Demak Regency, and Sidoarjo Regency locations. Each regency had 100 respondents, and data analysis was conducted using smartPLS. The study's results confirmed that GKS and GCD positively and significantly affect GWB and GEP directly and through GWB. The findings highlight the importance of Green Knowledge Sharing (GKS) and Green Career Development (GCD) practices in enhancing employee green performance